2019
DOI: 10.1016/j.jtcvs.2018.12.078
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the radial artery or the saphenous vein in addition to the bilateral internal mammary arteries on late survival: A propensity score analysis

Abstract: Background: Long-term survival benefits of full arterial revascularization with radial artery (RA) used in addition to bilateral internal mammary arteries (BIMA) compared with saphenous vein (SV) used in addition to BIMA has not been clearly defined.Methods: We retrospectively analyzed 660 3-vessel coronary artery disease subjects who received BIMA in addition to either RA (n ¼ 206) or SV (n ¼ 454) grafting in a period between June 1999 and November 2017. After propensity score matching, we obtained 190 matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…On one hand, several retrospective studies and one meta‐analysis, have reported benefits, in terms of long‐term survival of adding a third arterial graft to a BIMA strategy. On the other hand, among the three studies included in the present meta‐analysis and exploring the same issue, only the last one reported that adding a third arterial graft, in this case, the radial artery, provides a long‐term survival benefit. Also, a recent meta‐analysis failed to show a benefit of adding an arterial graft over a venous graft to BIMA for the right coronary artery …”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…On one hand, several retrospective studies and one meta‐analysis, have reported benefits, in terms of long‐term survival of adding a third arterial graft to a BIMA strategy. On the other hand, among the three studies included in the present meta‐analysis and exploring the same issue, only the last one reported that adding a third arterial graft, in this case, the radial artery, provides a long‐term survival benefit. Also, a recent meta‐analysis failed to show a benefit of adding an arterial graft over a venous graft to BIMA for the right coronary artery …”
Section: Discussionmentioning
confidence: 91%
“…Studies were excluded for the following reasons: no comparison between TAR and non‐TAR strategy (n = 32), sample population derived from a previously published and included series (n = 1), and lack of propensity score matching (n = 1). Consequently, 18 articles were included in our study . Mean age and mean body mass index of the included populations were 65.6 years (±7.6) and 27.1 (±1.7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations